Employment-related Physical Activity during Pregnancy: Birth Weight and Still Birth Delivery in Karachi, Pakistan - Sameera Ali Rizvi, Khadijah Abid, Nida Shoaib, Madiha Abid (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the association of employment related-physical activity during pregnancy with birth weight and still birth. Methods: A prospective cohort study was carried out in the four hospitals. All singleton pregnant women ≥20 weeks’ gestational age attending antenatal care at the tertiary care hospitals were selected. They were followed up from the 20th week of gestation till delivery. The outcomes of this study were low birth weight and stillbirth. The exposed women were those who were employed throughout the current pregnancy and were involved in excessive and hard physical activity at work while unexposed women were unemployed throughout the current pregnancy. Descriptive statistics included frequency, mean and standard deviation for continuous variables while categorical variables were assessed by computing frequencies and percentages. P values were calculated using Chi-Square/Fisher exact test and T Test. Results: The mean age of the pregnant females was 28.66±4.87 years. Excessive physical activity at work was significantly associated with low birth weight and stillbirth. The risk of low birth weight was 1.46 times higher among pregnant women with excessive physical activity (RR = 1.46, 95% CI=1.12-1.91). The risk of stillbirth is 2.85 times higher among pregnant women with excessive physical activity (RR=2.85, 95% CI=1.22-6.63). Conclusion: The study demonstrated a significant association between excessive physical activities on birth outcomes in employed pregnant females. A high percentage of females exposed to extensive physical activity ended up with low birth weight and stillbirth. Woman’s age during pregnancy, women’s education and husband’s education are significantly associated with birth outcomes. Keywords: Physical Activity, Employment, Low Birth Weight, Still Birth, Birth outcome